KASIBA SEBAGAI SALAH SATU KEBIJAKAN PEMERINTAH DALAM PENYEOIAAN PERUMAHAAN' - Ari Widyati Purwantiasning (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2007)
AbstractPeople growth and urbanization in urban area ha~' fmplied onincreasing of housing need. The problem' 'araises, sin'ce the,·, housingsupply islnwer than housing ,need, ' especfally', for,'middlelow ,'incomepeople.The government had beeniliilialed todevelO~ ,corehc)usespoficyand offered housing development 'subsidies, fli'roiJghKPR' (KredifPemilikan Ramah) for middle low 'income peoplE;:' Based on t~ispolicy,smafland middle scale housings were ser)arcitediy built 'by both publicand private developers, This situ3tionimplied 0/1 araising new problemssince 1he housingdevelopmenlspreadly' squatted"ihurban areas. Itimpacts on un~integratedpI2n:ljng and high cost' of infrastructuremaintenance.ltis important to promote a new approach to supply housing formiddle low income peopl~ that more appropriate to urban integratedplanning, named as KAS1BA (Kaw8san Slap Bangan). This paper aimsto describeKASIBA in the term of goal managemem, involved agents,and finance method.Keywords: KAS/BA, housing development, urban integratedplanning